A rare case of bilateral breast lobular carcinoma coexisting with primary breast follicular lymphoma - Nooshin Mirkheshti; Mahsa Mohebtash (Greater Baltimore Medical Center, 2019)
CLINICAL PRACTICE POINTS ● Co-existence of breast cancer and lymphoma is a rare condition. A few cases of synchronous breast ductal carcinoma and lymphoma have been reported in the literature. However, to our knowledge this is the first case report of a bilateral breast lobular carcinoma co-presenting with follicular lymphoma. ● Little is known about the pathophysiology of synchronous cancers of different tumor types, especially solid tumors co-existing with hematologic malignancies. In-depth review of these cases can shed light on underlying mechanism leading to synchronous cancer development.